Feeding a world population of more than eight billion people - J.C. Waterlow (Oxford University Press, 1998)
This book takes a critical look at the immediate challenges for feeding the population just a generation from now. Based on the 10th International Symposium sponsored by the Nutrition Committee and the Trustees of the Rank Prize Funds, the volume examines the full range of related issues, from food economics to resource allocation and crop yields. Beginning with an analysis of future food needs, the articles cover basic resources and constraints, applications of science to increase yield, the role of animal products in feeding eight billion people, and diverse social issues